Analysis of Financial Behavior and Motivation of Generation Z in Decision-Making for Gold Installment Products at Bank Syariah Indonesia (Case Study: Gen Z Customers in Medan City) - Tasya Nadilla; Anggraini, Tuti; Perdana Indra, Ahmad (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the financial behavior and intrinsic motivation of Generation Z in Medan City in choosing Gold Installment products at Bank Syariah Indonesia (BSI). Using a descriptive qualitative method with a phenomenological approach, data were obtained through in-depth interviews with 11 active customers. The findings show that customers perceive installment margins as a “disciplinary cost” that helps control consumptive behavior and encourages forced savings. The product also demonstrates vertical inclusivity, attracting both formal and informal workers. Motivation differs by gender and life-cycle, where men prepare marriage dowries, while women seek financial independence. Islamic economic rationality includes material and spiritual satisfaction